The determinants of mortgage delinquency - Reichenberger, Adam (Kansas State University, 2011)
The recent housing crisis has highlighted the need to better understand the determinants of mortgage default. Concerns about potential sizable differences in default rates by race and ethnicity as well as reports in the popular press regarding the propensity for rising numbers of homeowners to strategically default motivate a careful study of mortgage delinquency in America post-housing bubble. Using longitudinal data from the Panel Study of Income Dynamics (PSID), we examine borrowers in the years 2005, 2007 and 2009 and, controlling for a number of default-related variables, take a closer look at the characteristics of those delinquent on their mortgage by 2009. We find startling racial and ethnic gaps present as well as strong effects from children, education, and the presence of recourse/non-recourse laws in the state of residence on the likelihood of delinquency. In addition, we find evidence that strategic default plays a role in explaining the likelihood that a homeowner in 2005 will be delinquent on his or her mortgage by 2009.
Keywords: Mortgage delinquency; Demographics; Economics (0501)